Benzylammonium‐Mediated Formamidinium Lead Iodide Perovskite Phase Stabilization for Photovoltaics. (19th May 2021) - Alanazi, Anwar Q.; Almalki, Masaud H.; Mishra, Aditya; Kubicki, Dominik J.; Wang, Zaiwei; Merten, Lena; Eickemeyer, Felix T.; Zhang, Hong; Ren, Dan; Alyamani, Ahmed Y.; Albrithen, Hamad; Albadri, Abdulrahman; et al.
Abstract: There is an ongoing surge of interest in the use of formamidinium (FA) lead iodide perovskites in photovoltaics due to their exceptional optoelectronic properties. However, thermodynamic instability of the desired cubic perovskite (α‐FAPbI3 ) phase at ambient conditions leads to the formation of a yellow non‐perovskite (δ‐FAPbI3 ) phase that compromises its utility. A stable α‐FAPbI3 perovskite phase is achieved by employing benzylammonium iodide (BzI) and the microscopic structure is elucidated by using solid‐state NMR spectroscopy and X‐ray scattering measurements. Perovskite solar cells based on the FAPbI3 (BzI)0.25 composition achieve power conversion efficiencies exceeding 20%, which is accompanied by enhanced shelf‐life and operational stability, maintaining 80% of the performance after one year at ambient conditions. Abstract : A stable α‐FAPbI3 perovskite phase is achieved by employing benzylammonium iodide (BzI), which is elucidated by solid‐state NMR spectroscopy and X‐ray scattering measurements to obtain perovskite solar cells based on the FAPbI3 (BzI)0.25 composition with power conversion efficiencies exceeding 20% accompanied by enhanced shelf‐life and operational stability, maintaining 80% of the performance after one year at ambient conditions.